2011
DOI: 10.1364/oe.19.021050
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of the Raman scattering cross section of the breathing mode in KDP and DKDP crystals

Abstract: The spontaneous Raman scattering cross sections of the main peaks (related to the A1 vibrational mode) in rapid and conventional grown potassium dihydrogen phosphate and deuterated crystals are measured at 532 nm, 355 nm, and 266 nm. The measurement involves the use of the Raman line of water centered at 3400 cm-1 as a reference to obtain relative values of the cross sections which are subsequently normalized against the known absolute value for water as a function of excitation wavelength. This measurement en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
26
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 28 publications
3
26
0
Order By: Relevance
“…Nevertheless, we are confident that these disadvantages can be ameliorated through technical improvements, such as optimising the operating frequency to minimise the low thermal conductivity, precise control of the crystal temperature to ameliorate the small temperature acceptance, adjustment of the experimental parameters against TPA, and moderately changing the composition to prevent TSRS. It has been shown that deuterated KDP crystals can effectively decrease the TSRS gain compared with normal KDP crystals1820; a similar phenomenon was found in a comparison of deuterated ammonium dihydrogen phosphate (DADP) and ADP crystals19; the partial-doping method can also be applied to ADP crystals to lessen the TSRS. In fact, in current ICF facilities, the edges and corners of large aperture NLO crystal components have compound chamfers and bevels to avoid multiple passes of side-scattered light; this technique is effective for the decrease of TSRS.…”
Section: Resultsmentioning
confidence: 62%
“…Nevertheless, we are confident that these disadvantages can be ameliorated through technical improvements, such as optimising the operating frequency to minimise the low thermal conductivity, precise control of the crystal temperature to ameliorate the small temperature acceptance, adjustment of the experimental parameters against TPA, and moderately changing the composition to prevent TSRS. It has been shown that deuterated KDP crystals can effectively decrease the TSRS gain compared with normal KDP crystals1820; a similar phenomenon was found in a comparison of deuterated ammonium dihydrogen phosphate (DADP) and ADP crystals19; the partial-doping method can also be applied to ADP crystals to lessen the TSRS. In fact, in current ICF facilities, the edges and corners of large aperture NLO crystal components have compound chamfers and bevels to avoid multiple passes of side-scattered light; this technique is effective for the decrease of TSRS.…”
Section: Resultsmentioning
confidence: 62%
“…where c is the velocity of light in vacuum, M is the molecular density per cm 3 Temperature (K) Figure 5 Relative SRS gain coefficient of the ν 1 mode at different temperatures The Raman scattering cross section is proportional to the scattering intensity. So According to the above measured results, the relative SRS gain at different temperatures can be compared, as is shown in Fig.…”
Section: The Srs Gain Coefficient Of the ν 1 Modementioning
confidence: 99%
“…In large-aperture KDP crystal, the SRS especially the transverse stimulated Raman scattering (TSRS) can not only induce the energy loss, but also the damage to the optic components. 2,3 As we all know, the lattice vibration is related to temperature. So the Raman scattering property should be temperature-dependent, which is validated by a lot of researches concerning the temperature dependence of crystal Raman scattering, such as quartz, silicon, diamond, and GaN.…”
Section: Introductionmentioning
confidence: 99%
“…However, this solution is not applicable in the case of TSRS in KDP crystals. It is due to the fact that Raman linewidths in KDP are on the order of 600 GHz while Brillouin linewidths are 100 ~200 MHz [17]. Thus, over 45 THz of spectral broadening on the main laser beam would be required to suppress TSRS, which is far too large to support efficient frequency conversion, and the operating conditions in most ICF laser facilities.…”
Section: Introductionmentioning
confidence: 99%
“…At present, the most effective method to suppress TSRS is to replace KDP by the much more expensive DKDP. This choice stems from the fact that deuterating the KDP splits the totally symmetric breathing mode into two modes that have lower Raman cross section, thus decreasing the Raman scattering cross section and the SRS gain coefficient at the line center [17,18]. But besides the high cost of replacement, DKDP crystals are more vulnerable to laser-induced damage due to the intrinsic and impurity defects known to exist in DKDP [19][20][21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%